Magnesia doped Ag/Al2O3 - sulfur tolerant catalyst for low temperature HC-SCR of NOx - More, Pavan M.; Jagtap, Neelam; Kulal, Atul B.; Dongare, Mohan K.; Shubhangi B. Umbarkar (Applied Catalysis B-Environmental, 2014)
A series of magnesia doped Ag/Al2O3 catalysts were prepared by modified impregnation method using boehmite as alumina precursor. The prepared catalysts were characterized and tested for the SCR of NOx using propene as reductant under lean condition. Doping of magnesia improved the low temperature catalytic activity for HC-SCR of NOx as well as sulfur tolerance. Maximum 98% NO conversion with 100% selectivity for N-2 was obtained at 350 degrees C with 7% Mg doping to Ag/Al2O3. The improvement in low temperature activity and the sulfur tolerance has been correlated to decreased acidity after addition of magnesia to alumina support. In situ FTIR study showed that the deactivation in the presence of SO2 was due to the sulfation of silver and aluminum sites in Ag/Al2O3 catalyst, however its formation was suppressed in case of magnesia doped Ag/Al2O3 improving its sulfur tolerance. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: HC-SCR; Low temperature activity; NOx; Sulfur tolerance